South Asian masculinities : context of change, sites of continuity - Chopra,Radhika (Editor) Osella,Caroline (Editor) (Women Unlimited an associate of Kali for Women, 2004)
Selection of papers presented at the 16th European Conference on Modern South Asian Studies, University of Edinburgh, September 2000; chiefly on Indian men.